Analysis of the Relationship between Anemia and Learning Performance among Adolescent Girls at Madrasah Aliyah Negeri (MAN) 1 Gorontalo - Siti Baderan; Adrian Umboh; Jonesius Eden Manoppo (Lambung Mangkurat University, 2024)
Anemia in adolescence is one of the most common health problems worldwide, with an increasing prevalence. Anemia can cause psychomotor and cognitive disorders, affecting learning performance. This study aimed to analyze the relationship between anemia and learning performance among adolescent girls at Madrasah Aliyah Negeri (MAN) 1 in Gorontalo. This quantitative study employs a cross-sectional design. The subjects of this study were 120 adolescent girls, selected using the purposive sampling technique. Respondent characteristics included age; parental education, occupation, and income; as well as the respondent's pocket money. Data were obtained through interviews using a questionnaire, and anemia status was assessed through Hb tests using a digital hemoglobin test. Learning performance was assessed using the learning outcome report. Data analysis was conducted using a chi-square test and multivariate analysis with logistic regression. The results showed that the prevalence of anemia among adolescent girls was 8%. The analysis results indicated a significant relationship between anemia and learning performance (p-value = 0.013), with an odds ratio (OR) of 3.111, meaning that adolescent girls with anemia were at three times higher risk of having poorer learning performance compared to those without anemia. It can be concluded that anemia is associated with the learning performance of adolescent girls; thus, more care needs to be given to the health of adolescent girls in educational institutions.